Computer Vision Syndrome During SARS-CoV-2 Outbreak in University Students: A Comparison Between Online Courses and Classroom Lectures - Wang, Lixiang; Wei, Xin; Deng, Yingping (Frontiers in Public Health, 2021)
Purpose: To compare the prevalence of computer vision syndrome in university students of different teaching modes during the SARS-CoV-2 outbreak period. Methods: A cross-sectional survey study using the validated Computer Vision Syndrome Questionnaire in Chinese medical students of Sichuan University who took classroom lectures and same-grade foreign students from a Bachelor of Medicine & Bachelor of Surgery (MBBS) program who took online lectures with similar schedules. Results: A total of 137 responses from 63 Chinese students and 74 MBBS students were obtained. The highest frequency of digital screen time was 7-9 hours (43.24%, 32/74) for MBBS students and 2-4 hours (46.03%, 29/63) for Chinese students. The prevalence of computer vision syndrome among Chinese students and MBBS students was 50.79% and 74.32%, respectively (P=0.004). The average numbers of reported symptoms were 5.00±2.17 in Chinese students and 5.91±1.90 in MBBS students (P=0.01). The three most highly reported symptoms were “heavy eyelids” (53.97%), “dryness” (50.79%) and “feeling of a foreign body” (46.03%) in Chinese students and “dryness” (72.97%), “feeling of a foreign body” (62.16%) and “heavy eyelids” (58.11%) in MBBS students. The sum grades of computer vision syndrome had a moderate positive correlation with screen time (Spearman’s correlation coefficient= 0.386, P=0.000). The grades of symptoms of “feeling of a foreign body”, “heavy eyelids” and “dryness” showed a weak positive correlation with screen time (Spearman’s correlation coefficients were 0.220, 0.205, and 0.230, respectively). Conclusion: Online study may contribute to the prevalence of computer vision syndrome among university students.